2017
DOI: 10.1104/pp.17.01484
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical Inclusion Protein of Turnip Mosaic Virus Serves as a Docking Point for the Intercellular Movement of Viral Replication Vesicles

Abstract: Plant viruses move from the initially infected cell to adjacent cells through plasmodesmata (PDs). To do so, viruses encode dedicated protein(s) that facilitate this process. How viral proteins act together to support the intercellular movement of viruses is poorly defined. Here, by using an infection-free intercellular vesicle movement assay, we investigate the action of CI (cylindrical inclusion) and P3N-PIPO (amino-terminal half of P3 fused to Pretty Interesting Potyviridae open reading frame), the two PD-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…This dual construct expresses both 6K2-mCherry and GFP-HDEL from the infectious TuMV. The construct allows monitoring of the production of 6K2 vesicles in primarily infected cells (indicated by the presence of both GFP-HDEL and 6K2-mCherry) and in secondarily infected cells (indicated by the presence of 6K2-mCherry only; Agbeci et al, 2013;Jiang et al, 2015;Movahed et al, 2017). As indicated in Figure 2, the production of 6K2-mCherry in primary infection foci, as evidence by the production of green and red fluorescence, was first observed in both Col-0 and rhd3-8 plants after 7 dpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This dual construct expresses both 6K2-mCherry and GFP-HDEL from the infectious TuMV. The construct allows monitoring of the production of 6K2 vesicles in primarily infected cells (indicated by the presence of both GFP-HDEL and 6K2-mCherry) and in secondarily infected cells (indicated by the presence of 6K2-mCherry only; Agbeci et al, 2013;Jiang et al, 2015;Movahed et al, 2017). As indicated in Figure 2, the production of 6K2-mCherry in primary infection foci, as evidence by the production of green and red fluorescence, was first observed in both Col-0 and rhd3-8 plants after 7 dpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because knockout of the RHD3 gene leads to the formation of a "cable-like" nonbranched ER network (Chen et al, 2011;Zhang et al, 2013;Feng et al, 2016), it was suggested that the affected ER structure plays a role in the delayed movement of the Tomato spotted wilt tospovirus and its movement protein (Feng et al, 2016). However, it is known that the replication vesicles of TuMV are not only the site of viral replication, but also the vehicle for TuMV intercellular movement (Movahed et al, 2017). It has been suggested that replication incompetent DMVs and MVBs may play an important role in the systemic spread of TuMV (Wan et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the Potyvirus members, accumulating evidence shows that P3N-PIPO functions as a MP to mediate viral cell-to-cell movement (Choi et al, 2005;Chung et al, 2008;Wei et al, 2010b;Wen & Hajimorad, 2010;Vijayapalani et al, 2012;Cui et al, 2017). P3N-PIPO recruits CI to PD (Wei et al, 2010b;Deng et al, 2015;Movahed et al, 2017), while CI serves as a docking point for the intercellular movement of virus replication vesicles (Movahed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%